Pengaruh Akuntabilitas Pengelolaan Dana Desa pada Masa Pandemi Covid-19 dalam Theory Of Planned Behavior - Desy Wijayanti; Anik Malikah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the accountability of village fund management during the COVID-19 pandemic using the theory of planned behavior. The population in this study is officials of Tlekung Village, Mojorejo Village, and Torongrejo Village. The sample samples in this study used the Non Probability Sampling technique. The sample of this study was 166 respondents. Data analysis was performed using multiple linear regression methods. The results of this study show that (1) management attitudes have a positive and significant effect on carrying out accountable intentions in village fund management during the Covid-19 pandemic, (2) subjective norms have a positive and significant effect on carrying out accountable intentions in village fund management during the Covid-19 pandemic, (3) self-efficacy has a positive and significant effect on carrying out accountable intentions in village fund management during the Covid-19 pandemic.Keywords: The effect of attitude, subjective norms, self-efficacy on the implementation of the intention to act responsibly in managing village funds during the Covid-19 pandemic.